Non Linear Analysis of Reinforced Concrete Column Strengthened by Reinforced Concrete Jacketing with High Strength Steel - Imron Imron; Bambang Piscesa; Achfas Zacoeb (Institut Teknologi Sepuluh Nopember, 2022)
The strengthening column structure elements with reinforced concrete jacketing were chosen in this study because it is the most common and easy to apply practically to existing column structures. Modeling data using test specimens from Ersoy et. al by adhering to constitutive models of concrete materials from Attard and Stunge and Bilinear steel. The purpose is to perform non-linear analysis modeling through the behavior of the section of the RC column reinforced with RC jacket by taking into account the influence of interface slip and initial strain by using a two-dimensional sectional analysis approach with a fiber-based method made using MATLAB. Non-linear analysis was performed to obtain the moment-curvature relationship and validate the modeling results with the experimental model then make modeling variations based on the variations high strength steel reinforcement and evaluate the results in curvature ductility and index ductility. The prediction results showed a fairly good fit with the experimental results and modeling variations showed that the greater value of interface slip coefficient, the higher the curvature ductility and index ductility, the variation modeling using high-strength steel in longitudinal reinforcement can increase flexural, axial and lateral capacity, but it is lower in ductility, while using normal strength steel for longitudinal reinforcement and high strength steel for lateral reinforcement with tighter spacing provides higher ductility.